KONSEP MAQASHID AL-SYARI`AH: PERBANDINGAN ANTARA PEMIKIRAN AL-GHAZALI DAN AL-SYATHIBI - Suansar Khatib (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2018)
This article explains the comparison of maqashid al-shari'ah thinking between al-Ghazali and al-Syathibi. The purpose and core of all Islamic teachings (Qur'an and hadith) is benefit. The need to prioritize the benefit of religious texts and ijma in the Muamalah region and adat if there is a contradiction between the two. Benefits prepared by humans must be included in the benefit of the text if there is a contradiction between the two. Both of them also agreed that the benefit was intended, the essence returned to the protection of humans themselves, but according to al-Thufi maslahah is the most authoritative independent proposition to determine legal policy. Benefit is not an authoritative proposition to determine legal policy. Benefit is not a legal proposition, but as the core and purpose of a law. According to him all the Islamic Shari'ah teachings have a causal relationship (muamalah) with benefit in the customary territory and muamalah. Intellect (intellect) of normal human beings can also know and find benefit in the area of muamalah and adat (tradition) not in the area of worship